KONSEP MURAH HATI BERDASARKAN LUKAS 6:36 - Marlon Taung (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2021)
This paper discusses the meaning of generosity in Luke 6:36. The method used is library research, with the primary sources being the Bible, books, literature, and other sources related to the subject matter. The results showed that the meaning of generosity in Luke 6:36 is to love and forgive fellow human beings. Generosity is a command of God. All believers must practice God's order in concrete actions. Generosity also reflects the Father or is a God-like attribute. Therefore, living generous means expressing the presence of God during life with others.